The twelve topsy-turvy, very messy days of Christmas [large type] - Patterson, James, 1947-; Safran, Tad (Little, Brown and Company, 2022)
During the holiday season, a family of three, missing someone very dear to them, find their house filling up with unexpected guests, making Christmas memories to last a lifetime.